2007
DOI: 10.1016/s0929-6646(09)60256-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific Prevalence Rates of Phimosis and Circumcision in Taiwanese Boys

Abstract: Nonretractability of the prepuce was very common among the Taiwanese newborns. Among the school boys, the degree of preputial separation and exposure of glans increased with age and progressed even more rapidly in adolescence. Very few boys still suffered from unretractable prepuce by the age of 13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Ko et al . reported that the prevalence of circumcision in Taiwan was 7.2%~8.7% [26]. In this study, our findings indicated that circumcision of MSM provides a certain degree of protection against HIV-1 infection.…”
Section: Discussionsupporting
confidence: 53%
“…Ko et al . reported that the prevalence of circumcision in Taiwan was 7.2%~8.7% [26]. In this study, our findings indicated that circumcision of MSM provides a certain degree of protection against HIV-1 infection.…”
Section: Discussionsupporting
confidence: 53%
“…[2][3][4] These were sourced as follows. The PubMed search yielded 1455 "hits," of which 27 2,4,14,17,18,20,21,[23][24][25][27][28][29][30][33][34][35][37][38][39][41][42][43]45,46,48,49 fulfilled the inclusion criteria. Google Scholar yielded 4 further articles.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…[ 18 ] The ShangRing ® has also been pre-qualified for minimum age of 13 years. [ 19 ]Although there are reports showing that the incidence and prevalence of phimosis is higher in younger males,[ 20 ],[ 21 ],[ 22 ] none of these studies were conducted in countries with high HIV prevalence and low circumcision rate where VMMC roll out is recommended. To our knowledge, this is the first study to determine the prevalence of preputial and penile scrotal abnormalities among boys between 8 and 18 years of age who present for VMMC.…”
Section: Introductionmentioning
confidence: 99%